If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 47 + -7x = 20x + 17 Reorder the terms: 47 + -7x = 17 + 20x Solving 47 + -7x = 17 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 47 + -7x + -20x = 17 + 20x + -20x Combine like terms: -7x + -20x = -27x 47 + -27x = 17 + 20x + -20x Combine like terms: 20x + -20x = 0 47 + -27x = 17 + 0 47 + -27x = 17 Add '-47' to each side of the equation. 47 + -47 + -27x = 17 + -47 Combine like terms: 47 + -47 = 0 0 + -27x = 17 + -47 -27x = 17 + -47 Combine like terms: 17 + -47 = -30 -27x = -30 Divide each side by '-27'. x = 1.111111111 Simplifying x = 1.111111111
| 6p+21/2=141/2 | | 27+9c=12+4c | | 9-7x=22-14x | | h/2=6 | | 3x=10+13x | | 8=9x-5 | | 54=-9t | | -10(x+4)+50=15-15 | | 2r^2+6r-3=0 | | 5+5c=12+6c | | 5x+6=69-10x | | y/3=-12 | | 3t+6=24 | | x+0.9=0.7 | | (x^2+2x-8)(x+1)=0 | | x^3-3x^2+4x+-84=0 | | 31=-x | | -2+14=15x-3-14 | | 3(x-2)-5c=-4x+4 | | 4(2x+1)=2x-8x | | 15=8+v | | 2/5x=9-5 | | -10y-11=-2 | | (6a-5b+c-7d)7= | | 17x-8=12x-13 | | -6y-1=-5y-3 | | 4x-2=-18 | | 5x^2=2-9 | | 1/2y=3 | | b^2+8b+15= | | 2x-3/6-8-x/9=x+3/18 | | 6x12/36 |